THEOLOGY AND TECHNOLOGY: Working to End Gender-Based Violence - Fitz Gerald, Marianne Tierney (Asian Horizons, 2016)
Gender-based violence is among the greatest challenges in the world. Theologians and ethicists need to be more involved in promoting the rights of women and working to eradicate this evil. There are a number of ways technology can support the efforts of these theologians. Although innovators and entrepreneurs have, in the past, created applications that can be used to protect women, these advances do not address the root causes of this violence. This article suggests that theologians and innovators work together to address the cultural norms that have allowed this type of violence to escalate all over the world. Theologians can use Catholic Social Thought and other important church teachings to affirm the inherent dignity of women. In order to spread this message and find greater support, they can seek new partnerships with technology. Although technology and theology seem like unlikely partners, they can work together to develop new strategies that protect women and build a better future.